Path Planning and Obstacles Avoidance in Dynamic Workspace Using Polygon Shape Tangents Algorithm - Ramadhan, Duaa Ahmed; Al-Mayyahi, Auday; Rashid, Mofeed Turky (Iraqi Journal for Electrical and Electronic Engineering, 2021)
This paper presents the design of a path planning system in an environment that contains a set of static and dynamic polygon obstacles localized randomly. In this paper, an algorithm so-called (Polygon shape tangents algorithm) is proposed to move a mobile robot from a source point to a destination point with no collision with surrounding obstacles using the visibility binary tree algorithm. The methodology of this algorithm is based on predicting the steps of a robot trajectory from the source to the destination point. The polygon shapes tangent algorithm is compared with the virtual circles’ tangents algorithm for different numbers of static and dynamic polygon obstacles for the time of arrival and the length of the path to the target. The obtained result shows that the used algorithm has better performance than the other algorithms and gets less time of arrival and shortest path with free collision.